2020
DOI: 10.1111/jfb.14272
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the skeleton and skeletal deformities in zebrafish (Danio rerio) linked to rearing density

Abstract: The teleost zebrafish (Danio rerio), an established model for human skeletal diseases, is reared under controlled conditions with defined parameters for temperature and photoperiod. Studies aimed at defining the proper rearing density have been performed with regard to behavioural and physiological stress response, sex ratio and reproduction. Studies concerning the effect of rearing density on the skeletal phenotype are lacking. This study is designed to analyse the response of the skeleton to different rearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 88 publications
(122 reference statements)
2
51
1
Order By: Relevance
“…Bird and Mabee [ 40 ] serve as reference for normal skeletal development in zebrafish. In addition several publications define malformations of the zebrafish axial skeleton [ 41 , 42 , 43 ]. The absence of any of the described malformation is regarded as normal in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bird and Mabee [ 40 ] serve as reference for normal skeletal development in zebrafish. In addition several publications define malformations of the zebrafish axial skeleton [ 41 , 42 , 43 ]. The absence of any of the described malformation is regarded as normal in this study.…”
Section: Resultsmentioning
confidence: 99%
“…This could explain why spines are twisted but vertebral centra are not affected in LP zebrafish. In laboratory zebrafish strains, undulated spines also occur linked to conditions other than P deficiency such as increased rearing density [ 43 ] or disturbed somite formation [ 66 ]. In addition, it has been suggested that spine deformities relate to musculature impairment [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, higher holding densities can cause increased mortality during the early juvenile phase, 18 decreased growth during the first 3 weeks to 3 months, 51,53 and increased occurrence of skeletal deformities during the first 3 months. 54 To optimize the growth, fish larvae should be held at densities between 12 and 22 fish/L according to Delomas and Dabrowski, 53 and at 9…”
Section: Rearing Larvae and Juvenilesmentioning
confidence: 99%
“…In zebrafish, Danio rerio (Hamilton 1822), vertebral column shortening and vertebral fusions are exhibited by type I collagen mutants, as well as by individuals with knockout alleles in two genes involved in type I collagen processing [107]. At the same time, the increased frequency of vertebral deformities in wild-type zebrafish is induced by high rearing densities [108]. The stumpbody phenotypes with the shortened vertebral column in channel catfish Ictalurus punctatus (Rafinesque 1818) [109] and blue tilapia Oreochromis aureus (Steindachner 1864) [12,110] are described as not heritable.…”
Section: Factors Responsible For Abnormal Body Shortening In Fishmentioning
confidence: 99%